Influence of the capping material on pyridine-induced chemical interface damping in single gold nanorods. Issue 8 (11th March 2019) - Moon, Seong Woo; Ha, Ji Won
Abstract : Chemical interface damping (CID) is one of the plasmon decay processes that occur in gold nanoparticles. Abstract : Chemical interface damping (CID) is one of the plasmon decay processes that occur in gold nanoparticles. With the aim of exploring new functional groups that can induce CID as an alternative to thiol groups, we performed dark-field (DF) scattering studies of gold nanorods (AuNRs) using pyridine as adsorbate. We found that the adsorption of pyridine molecules on single AuNRs though nitrogen–gold interactions leads to an increase of the localized surface plasmon resonance (LSPR) linewidth. However, pyridine molecules were not adsorbed effectively on AuNR surfaces having a capping reagent. This study allows us to gain insight into the effect and role of the capping reagent in pyridine-induced CID. Furthermore, pyridine was revealed to induce a strong CID through the interaction of the nitrogen atom with the Au surface, provided the capping material was previously removed from the AuNRs by oxygen plasma treatment. Finally, we demonstrated that CID could be used to sense pyridine and its derivatives in real-time.